The Role of Strengthening Vocabulary Memorization in Facilitating Arabic Language Learning Students Babul Mu'arrif Jambi Islamic Boarding School - Rahmatan, Madah; Sani, Nurhikmah; Alvio JH, Depaty; Azka Harlek Putra, Muhammad Hila; Salsabila, Fakhrina (Fakultas Tarbiyah dan keguruan- UIN Ar-Raniry, 2023)
Word vocabulary is the ability that a person uses to communicate and interact with each others properly and correctly. The information obtained in communication affects the understanding obtained. With the existence of vocabulary affecting one's use in using spoken Arabic or learning Arabic, the strengthening of Arabic vocabulary in improving Arabic learning becomes something that must be prioritized and understood, and understood to make it easier for students to learn Arabic lessons properly and correctly. This research was conducted in an Islamic boarding school educational institution. Babul Mu'arrif Islamic Boarding School is located in Sangi Lubuk Pauh Hamlet, Timbolasi Village, Bathin III Ulu District, Bungo District, Prov. Jambi. The approach taken is an approach through observational case studies that prioritize data collection techniques through value observation and the role of vocabulary in facilitating Arabic language learning, interviews, and documentation. The research methods used are Planning, implementation, data analysis, and evaluation. Efforts to strengthen the memorization of Arabic vocabulary carried out by educators or teachers at the Babul Mu'arrif Islamic Boarding School aim to make it easier for students or students to learn Arabic lessons. Upaya is carried out by the babul mu'arrif Islamic boarding school giving vocabulary starts from providing vocabulary when Arabic Subjects, Islamic Subjects, and Islamic Boarding School Activities. Problems and problems that arise will certainly be felt by both parties. Both from the teaching or teacher workforce and the students or students. The problems and problems that exist in the process of strengthening the memorization of Arabic vocabulary are inadequate educational facilities.